Pengaruh Kualitas Pembelajaran, Kualitas Tutor dan Motivasi Terhadap Prestasi Belajar Mahasiswa Universitas Terbuka Palembang - Heldiono Heldiono; Indawan Indawan; Sakdiah Wati (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
This study aims to determine the effect of learning quality, tutor quality and motivation both jointly and partially on student achievement at the Palembang Open University (Pokjar Pangkalan Lampam - Tulung Selapan. The research approach is quantitative research with associative research type. The population of this study is 186. students. The sampling method for probability with the Stratified Random Sampling method. The sample of this study was calculated using the Slovin formula with an error rate of 10%, the number of samples was 65 students as respondents. The first sample was tested using the Instrument Validity Test and the Instrument Reliability Test. The analysis model used in this study is multiple linear regression analysis. The regression calculation can be Y = -1.649 + 0.567X1 + 0.351X2 + 0.457X3. Interpretation of the multiple regression equation regarding the influence of the Learning Quality Variables (X1), Tutor Quality (X2) and Learning Motivation (X3), on Student Learning Achievement (Y). The results of the calculation of the three coefficients of the independent variable are positive, this indicates a positive linear relationship (unidirectional), meaning that the quality of learning, quality of tutors and learning motivation, the better, the better the student achievement. Obtained a correlation coefficient (R) of 0.712, with a level of closeness between variables of 0.712 which is in the interpretation of the correlation value (0.60-0.799) means that the relationship between the two variables is significant and the level of closeness is strong. The coefficient of determination value R2 = 0.507, which means that the variables of Learning Quality, Tutor Quality, and Learning Motivation are able to explain the Student Learning Achievement Variables of 0.507 or 50.7%, while the remaining 49.3% is explained by other factors not examined.